Fundamental of medical surgical and special senses nursing procedures - Shahadan, Siti Zuhaidah (Kulliyyah of Nursing (KON), IIUM, 2025)
"Welcome to 'Nursing Procedures: Fundamental of Medical Surgical and Special Senses Nursing,' a comprehensive guide explicitly tailored for second-year Bachelor of Nursing students. This procedure book is meticulously designed to focus solely on nursing procedures pertinent to wound management, medication administration, eye, ears, nose, and throat (ENT) procedures, offering concise, step-by-step instructions for essential clinical tasks. This resource aims to equip students with the foundational skills necessary to provide effective client care within these critical physiological domains by honing in on practical procedures. Each procedure is presented with clarity and precision, facilitating mastery and confidence in clinical practice. Whether in a classroom or clinical setting, this book serves as an invaluable companion, empowering students as they progress in their nursing journey."